PERILAKU MAKAN DAN MINUM PADA ANAK ITIK MAGELANG (Anas plathyrhynchos) PASCA TETAS DARI INDUK YANG DIBERI PERLAKUAN KURKUMIN, CAHAYA PUTIH DAN CAHAYA MERAH - Fajar Sara Kusumawati; Silvana Tana; Enny Yusuf Wachidah Yuniwarti (Jurnal Akademika Biologi, 2017)
This study aims to examine the effect of white light treatment, red light, curcumin with white light and curcumin with red light on the parent to the eating and drinking behavior of magelang ducks (Anas plathyrhynchos). This study uses 16 magelang ducklings consisting of 4 treatments. The observations in this study were from 4 groups namely A.1B1 which is the duckling of the original treatment given white light, A1B2 which is the duck of the parent treatment given red light, A2B1 which is the duck of the parent treatment given curcumin dose 18 mg / kg and white light, and A2B1 which is a duck from the parent treatment given curcumin dose 18 mg / kg and white light. Parameters measured in this study were data of eating behavior and data of drinking behavior of magelang ducks (Anas plathyrhynchos). This research is analyzed by descriptive analysis. The conclusions of this study are eating and drinking behavior in post-hatch children duck treated from the parent who was given a white light that is decreased the frequency of eating and drinking in the afternoon in the second week, eating and drinking behavior in post-hatch ducks after treatment of the mother given red light that is decreased the frequency of eating and drinking in the morning in the second week, eating and drinking behavior in post-tetas duck treated from the parent who was given curcumin and white light that decreased the frequency of eating in the afternoon while the frequency of drinking tends to decline throughout the day in the second week as well as eating and drinking behavior in post-tetas ducklings treated from the parent who was given curcumin and red light that increased the frequency of eating throughout the day at week II and decreased the frequency of drinking during the day on week II.Key words: feeding behavior, drinking behavior, magelang duck, curcumin, red light and white light